EFISIENSI PENGGUNAAN KAS DAN PENGGUNAAN ASET TERHADAP LABA PT ACE HARDWARE INDONESIA TBK PERIODE 2014 - SEPTEMBER 2023 - Belinda, Jane Metta; Anggraini, Vanya Almira; Calista, Kanaya; Manurung, Elizabeth T (Universitas Prof.Hazairin,SH Bengkulu, 2024)
Increasingly tight business developments and competition encourage companies to increase the efficiency and effectiveness of their cash and asset management. PT Ace Hardware Indonesia Tbk, as a leading retail company, needs to optimize its inventory management to increase profits. Cash turnover and total assets turnover are two important indicators for measuring the efficiency of cash and asset management. This research aims to examine the effect of cash turnover and total assets turnover on the profits of PT Ace Hardware Indonesia Tbk. This research uses secondary data from the quarterly financial reports of PT Ace Hardware Indonesia Tbk for the period 2014 to September 2023. Data analysis was carried out using multicollinearity tests, f tests, t tests, determinant coefficients, and multiple linear regression analysis. Simultaneously, the research results show that cash turnover and total assets turnover have an influence on PT Ace Hardware Indonesia's profits for the period 2014-September 2023. The results of the partial total assets research have a positive and significant influence while partial cash turnover has a negative and significant influence on PT Ace Hardware Indonesia's profit for the period 2014-September 2023.